Utilization of Family Planning Methods and associated factors among women of reproductive age group in Sunsari, Nepal - Mandal, Punam Kumari; Yangden, Namita; Rai, Bhumika; Niraula, Achala; Subedi, Sabitra (Janaki Medical College Journal of Medical Science, 2022)
Background and objectives: Family planning not only improves women’shealth but also promotes gender equality, better child health, and education, including poverty reduction. Therefore, the objective of this study was to assess the utilization of family planning methods and associated factors in Sunsari, Nepal. Materials and methods: A cross-sectional analytical study was conducted among women of the reproductive age group (15-49 years) in Sunsari in 2020. Non-probability purposive sampling was used to collect information from 212 respondents through face-to-face interviews using a Semi-structured interview schedule from ward no 1 of Barju rural municipality. Descriptive and inferential analysis (binary logistic regression)were used to find the association of utilization of family planning methods with selected demographic variables. All the variables with a p-value <0.1 in bivariate analysis were included in multivariate analysis. A p-value of <0.05 was considered to indicate statistical significance at a level of significance of 5%. Results: This study showed that the mean age and standard deviation of the respondents was 26±7.03 and 91.5 % of respondents’ age at marriage was less than 20 years.Likewise,67.5% of respondents use any methods of family planning and 55.2% of respondents use family planning services from the government health facility. Furthermore, education ((AOR 1.579, CI 1.013-2.462), husband’s occupation (AOR1.095,CI 0.744-1.610), type of family ((AOR 2.741, CI 1.210-6.210), and no of the living son ((AOR 0.259, CI 0.077-0.872) are the factors associated with the utilization of family planning methods. Conclusion: This study concludes that two-thirds of the reproductive age women utilize family planning methods. Furthermore, education, husband’s occupation, type of family, and no of living son are the factors associated with the utilization of family planning methods. This reflects that awareness through mass media including behavioral communication is needed to increase the utilization of family planning methods.